Detection of antigens and IgM antibodies for rapid diagnosis of viral infections: a WHO Memorandum (1979)
This Memorandum describes recent progress in the development of simplified and rapid laboratory technology and reviews currently available methods for the direct detection of viral antigens in clinical material and/or quantification of specific IgM antibody in acute serum specimens. Particular emphasis is given to such infections as viral hepatitis, rotavirus gastroenteritis, viral infections of the skin, genital, and respiratory tracts, and rabies. In addition, the standardization and quality control of reagents are discussed and recommendations are made.